Eco-friendly modification and antibacterial functionalization of viscose fabric. Issue 8 (3rd August 2017) - Ibrahim, N. A.; El-Zairy, E. M. R.; Eid, B. M.
Abstract: Pretreatment of viscose fabric with monochlorotraizinyl β-cyclodextrin (MCT-βCD), as an eco-friendly modifying agent, is accompanied by creation of hosting nanocavities onto the cellulose structure thereby enabling inclusion of certain antibacterial agents namely triclosan, as a classic agent, and AgNO3, as well as bioactive agents like green tea extract and Aloe vera gel. The efficiency of hosting the nominated antibacterial agents to confer antibacterial functionality is governed by the type of modification method and follows the decreasing order: exhaustion > pad-steam fixation > pad-dry-cure. The imparted antibacterial functionality of MCT-βCD-loaded fabric samples is determined by type of the hosted antibacterial agent into cavities of βCD and follows the decreasing order: AgNO3  > green tea extract > triclosan > Aloe vera gel. Nitrogen content analysis, FTIR spectra, SEM image and EDX spectrum of Ag-loaded fabric sample confirmed the impact of suggested treatment sequence on the chemical and surface properties of the functionalized viscose fabric. The results also demonstrate that the imparted antibacterial activity against S. aureus (G+ve) and E. coli (G−ve) bacteria slightly decreased after 15 washing cycles.